A comparative study on mechanical properties of coir fiber reinforced polymer composites filled with calcium carbonate particles. (2020) - Rajamuneeswaran, S.; Vairamuthu, J.; Nagarajan, S.; Stalin, B.; Jayabal, S.
Abstract: The current work is a study on the comparison of mechanical properties of different thermosetting polymers reinforced with coir fiber and calcium carbonate filler materials. Coir fiber is the load-carrying member in the reinforced composites and particle Calcium Carbonate (CaCO3 ) is used to get better the mould adhesion together of the composites. From the variety of thermoset polymers such as epoxy, Polyester, and vinyl ester are preferred in this present investigation and the mechanical behaviours (tensile strength, flexural strength, and impact strength) are calculated for the parameters of the varying compositions of Fiber Length (FL), Fiber Diameter (FD), Fiber Content (FC), and Filler Content (FLC).